Promosi Produk Kuliner Melalui Instagram - RD. Salma Widyadhana; Anne Ratnasari (Bandung Conference Series: Communication Management, 2022)
Abstract. In this era of globalization, the culinary business has experienced very significant growth, one of which is in the city of Bandung. The Parlor is one of the businesses in the culinary field in the city of Bandung, which has its own uniqueness in terms of serving food and in terms of place. The purpose of this study is to find out how to present culinary product advertisements on Instagram, promote product sales, product promotion barriers and efforts to overcome them, as well as the reasons for choosing mainstay features. This study uses a qualitative research method with a case study approach. The data collection techniques used were observation, interviews, documentation, and literature study. The subjects of this research are Operations Manager, Social Media Marketing and Consumers of The Parlor. The results of the research found by researchers are that in promoting their products, The Parlor provides product advertisements through Instagram such as new menus, saving packages, free product promos. Then in carrying out its sales promotion activities, The Parlor creates interesting content to introduce and market the available products. Obstacles felt when promoting products directly and Instagram algorithms that are not appropriate in uploading product promotional content. Efforts to overcome these obstacles are by relying on online promotional activities assisted by disseminating product promotional content by personal Instagram accounts of employees and other The Parlor staff in order to reach a wider target audience. Abstrak. Di era globalisasi ini bisnis kuliner mengalami pertumbuhan yang sangat signifikan, salah satunya di kota Bandung. The Parlor merupakan salah satu usaha dibidang kuliner di kota Bandung, yang memiliki keunikan tersendiri dari segi menyajian makanan dan segi tempat. Tujuan penelitian ini untuk mengetetahui bagaimana penyajian iklan produk kuliner di instagram, promosi penjualan produk, hambatan promosi produk dan upaya mengatasinya, serta alasan memilih fitur-fitur andalan. Penelitian ini menggunakan metode penelitian kualitatif dengan pedekatan studi kasus. Teknik pengumpulan data yang digunakan adalah, observasi, wawancara, dokumentasi, dan studi kepustakaan. Subjek penelitian ini yaitu Manager Operasional, Marketing Media Sosial dan Konsumen The Parlor. Hasil penelitian yang ditemukan oleh peneliti yaitu dalam melakukan promosi produknya The Parlor memberikan penyejian iklan produknya melaui Instagram seperti menu baru, paket hemat, promo gratis produk. Kemudian dalam melakukan kegiatan promosi penjulannya The Parlor membuat konten yang menarik guna memperkenalkan dan memasarkan produk yang tersedia. Hambatan yang dirasakan saat melakukan promosi produk secara langsung dan algoritma Instagram yang tidak sesuai dalam mengunggah konten-konten promosi produk. Upaya mengatasi hambatan tersebut yaitu dengan mengandalkan kegiatan promosi secara online dibantu dengan menyebar luaskan konten promosi produk oleh akun Instagram milik pribadi karyawan dan staff The Parlor lainnya agar mencapai target khalayak yang lebih luas.